Răspuns:
1). Ma=
[tex] = \frac{ (\sqrt{26} - 1)( \sqrt{26} + 1)}{2} = \frac{ \sqrt{26 ^{2} } - 1 {}^{2} }{2} = \frac{26 - 1}{2} = 13 - 1 = 12[/tex]
Mg=
[tex] \sqrt{( \sqrt{26} - 1)( \sqrt{26} + 1) } = \sqrt{ \sqrt{26 {}^{2} } - 1 {}^{2} } = \sqrt{26 - 1} = \sqrt{25} = 5[/tex]
Pe restul nu am timp sa le fac.Sper că te-am ajutat sa înțelegi cum se fac.
[tex]( \sqrt{26} - 1)( \sqrt{26} + 1) = \sqrt{26 {}^{2} } - 1 {}^{2} [/tex]
Acesta e o formula pe care ar trebui sa o ști
acea cu
[tex](a - b)(a + b) = a {}^{2} - b {}^{2} [/tex]